Services Trade and Policy - Joseph F. Francois; Bernard Hoekman (Johannes Kepler University of Linz, Department of Economics, 2009)
Since the mid-1980s a substantial body of research has taken shape on trade in services. Much of this is inspired by the WTO or regional trade agreements, especially the EU. However, an increasing number of papers focus on the impacts of unilateral services sector liberalization. The literature touches on important linkages between trade and FDI in services and the general pattern of productivity growth and industrial development. This paper surveys the literature on services trade, focusing on contributions that investigate the determinants of international trade and investment in services, the potential gains from greater trade (and liberalization) and efforts to cooperate to achieve such liberalization through trade agreements. There is increasing evidence that services liberalization is a major potential source of welfare gains, and that the performance of service sectors, and thus services policies, may be an important determinant of trade volumes, the distributional effects of trade, and economy-wide growth. At the same time, they are also an important source of increasing political unease about the impacts of globalization on labor markets.
Keywords: F1; F2; F5; L80; 330; trade in services; WTO; GATS; trade agreements; economic development; services and growth; modes of supply; trade and FDI linkages; foreign affiliates trade; Internationaler Dienstleistungsverkehr; Direktinvestition; Handelsabkommen; Außenhandelsliberalisierung; Entwicklung; Produktivität; GATS; Welt